Fast co-pyrolysis of a massive Naomaohu coal and cedar mixture using rapid infrared heating. (1st February 2020) - Zhu, Jialong; Jin, Lijun; Luo, Yanwei; Hu, Haoquan; Xiong, Yankun; Wei, Baoyong; Wang, Dechao
Highlights: Fast co-pyrolysis of a massive Naomaohu coal and cedar mixture was conducted. Infrared-heated technique can obviously enhance the heating rate up to 1200 °C/min. Cedar can efficiently act as hydrogen donor to enhance light tar content. Increasing of single-ring phenolics is mainly responsible for the upgraded tar. Abstract: Few studies on co-pyrolysis of a massive low-rank coal and biomass mixture with a high heating rate were conducted. This study adopted a novel infrared heating technique to minimize the secondary reactions process and further to explore the co-pyrolysis interactions of primary volatiles-volatiles from Naomaohu coal and cedar, based on co-pyrolysis products distribution, tar quality and compositions, char compositions at varied pyrolysis temperatures and blending ratios. The results show that infrared heating technique was successfully used to confirm the existence of synergies from primary volatiles of coal and biomass. The highest coal tar yield in the infrared-heated reactor with 1200 °C/min is 20.27 wt%, which is 1.54 times as the Gray-King assay. Higher cedar content can promote the generation of char and suppress the pyrolysis of NMH coal. At the pyrolysis temperature of 600 °C, light tar content in tar exhibited an increasing trend from 58.0 wt% to 75.5 wt% with the cedar content, and the best synergistic performance was obtained at 75% of cedar content. In addition, the significantly higher methyl-contained phenols and naphthalenes and lower CH4 revealed the fact that cedar can obviously act as hydrogen donor during co-pyrolysis process. The analysis of char compositions shows that the H has been transferred to gas and liquid products from solid char during co-pyrolysis, which can well interpret the improvement of tar quality.